Bioactivity and biomedical applications of pomegranate peel extract: a comprehensive review - Du, Jinsong; Wang, Heming; Zhong, Lingyun; Wei, Shujie; Min, Xiaoqiang; Deng, Hongyan; Zhang, Xiaoyan; Zhong, Ming; Huang, Yi (Frontiers in Pharmacology, 2025)
Pomegranate peel is a by-product generated during the processing of pomegranate (Punica granatum L.) fruit, accounting for approximately 50% of the total mass of the fruit. Although pomegranate peel is usually regarded as waste, it is rich in various bioactive metabolites such as polyphenols, tannins, and flavonoids, demonstrating significant medicinal and nutritional value. In recent years, Pomegranate peel extract (PPE) has shown broad application prospects in the biomedical field due to its multiple effects, including antioxidant, anti-inflammatory, antibacterial, anti-apoptotic properties, and promotion of cell regeneration. This review consolidates the major bioactive metabolites of PPE and explores its applications in biomedical materials, including nanodrug carriers, hydrogels, and tissue engineering scaffolds. By synthesizing the existing literature, we delve into the potential value of PPE in biomedicine, the challenges currently encountered, and the future directions for research. The aim of this review is to provide a scientific basis for optimizing the utilization of PPE and to facilitate its broader application in the biomedical field.